STDP in the developing sensory neocortex - Larsen, Rylan S.; Rao, Deepti; Manis, Paul B.; Philpot, Benjamin D. (Frontiers in Synaptic Neuroscience, 2010)
Spike timing-dependent plasticity (STDP) has been proposed as a mechanism for optimizing the tuning of neurons to sensory inputs, a process that underlies the formation of receptive field properties and associative memories. The properties of STDP must adjust during development to enable neurons to optimally tune their selectivity for environmental stimuli, but these changes are poorly understood. Here we review the properties of STDP and how these may change during development in primary sensory cortical layers 2/3 and 4, initial sites for intracortical processing. We provide a primer discussing postnatal developmental changes in synaptic proteins and neuromodulators that are thought to influence STDP induction and expression. We propose that STDP is shaped by, but also modifies, synapses to produce refinements in neuronal responses to sensory inputs.